Health information science : Second International Conference, HIS 2013, London, UK, March 25-27, 2013. Proceedings - Liu, Xiaohui; He, Jing; Klawonn, Frank; Yao, Guiqing; Huang, Guangyan (Lecture Notes in Computer Science, 2013)
This book constitutes the refereed proceedings of the Second International Conference on Health Information Science, HIS 2013, held in London, UK, in March 2013. The 20 full papers presented together with 3 short papers, 3 demo papers and one poster in this volume were carefully reviewed and selected from numerous submissions. The papers cover all aspects of health information sciences and systems that support the health information management and health service delivery. The scope of the conference includes 1) medical/health/biomedicine information resources, such as patient medical records, devices and equipments, software and tools to capture, store, retrieve, process, analyse, and optimize the use of information in the health domain, 2) data management, data mining, and knowledge discovery, all of which play a key role in the decision making, management of public health, examination of standards, privacy and security issues, and 3) development of new architectures and applications for health information systems.